Films from resistant starch-pectin dispersions intended for colonic drug delivery - Bagliotti Meneguin, Andréia [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Evangelista, Raul Cesar [UNESP] (Elsevier, 2014)
Free films were obtained by the solvent casting method from retrograded starch-pectin dispersions at different polymer proportions and concentrations with and without plasticizer. Film forming dispersions were characterized according to their hardness, birefringence and rheological properties. The polymer dispersions showed a predominantly viscous behavior (G″ > G′) and the absence of plasticizers lead to building of stronger structures, while the occurrence of Maltese crosses in the retrograded dispersions indicates the occurrence of a crystalline organization. Analyses of the films included mechanical properties, thickness, superficial and cross sectional morphology, water vapor permeability, liquid uptake ability, X-ray diffractometry, in vitro dissolution and enzymatic digestion. The high resistant starch content (65.8-96.8%) assured the resistance of materials against enzymatic digestion by pancreatin. Changes in the X-ray diffraction patterns indicated a more organized and crystalline structure of free films in relation to isolated polymers. Increasing of pectin proportion and pH values favored the dissolution and liquid uptake of films. Films prepared with lower polymer concentration presented better barrier function (WVP and mechanical properties). © 2013 Elsevier Ltd. All rights reserved.
Keywords: Dissolution; Enzymatic digestion; Free film; Pectin X-ray diffraction; Resistant starch; Cross-sectional morphology; Crystalline organization; Enzymatic digestions; Free films; Polymer concentrations; Solvent casting method; Water vapor permeability; Dispersions; Drug delivery; Liquids; Mechanical properties; Plasticizers; Polymers; Reinforced plastics; Solvents; Starch; X ray diffraction; X ray diffraction analysis; Polymer films; Lychnis chalcedonica